Atlet Perempuan Dalam Budaya Patriarki: Studi Pada Atlet Bulutangkis Putri Unit Kegiatan Olahraga UIN Sunan Ampel Surabaya - Argadilla, Rya Chitra (Universitas Islam Negeri Sunan Ampel, 2021)
This research was focused on the presence of female athletes at UKOR (Sports Activity Unit) State Islamic University of Sunan Ampel Surabaya who appeared with various achievements, their efforts to maintain achievement among male athletes, and their strength to always align their position with male athletes so as not to be easily underestimated. The research problems of this research were discussion of man athletes’ view of female athletes, discussion of gender relations both of male and female athletes and how female athletes could realize gender. Therefore, the methodology of this research was descriptive qualitativeby using observations, interviews and documentations as the data collections. This research used the theory of liberal feminism to analyze this phenomenon. The findings in this researchwere: (1) Female athletes in the management of the UKOR (Sports Activity Unit) were equal and had the same portion as male athletes. (2) Female athletes had the same opportunity in making decisions and receive the same treatment during training and discussions with male athletes. (3) The tolerance both of them was very good.